2015
DOI: 10.1002/wnan.1364
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticles: the future of nanomedicine

Abstract: Polymeric nanoparticles (NPs) are one of the most studied organic strategies for nanomedicine. Intense interest lies in the potential of polymeric NPs to revolutionize modern medicine. To determine the ideal nanosystem for more effective and distinctly targeted delivery of therapeutic applications, particle size, morphology, material choice, and processing techniques are all research areas of interest. Utilizations of polymeric NPs include drug delivery techniques such as conjugation and entrapment of drugs, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
249
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(251 citation statements)
references
References 227 publications
(251 reference statements)
0
249
0
2
Order By: Relevance
“…Nanoparticles may be engineered from biological macromolecules (proteins, DNA, RNA), lipids, polymers, semiconductors, metals, or a vast number of possible combinations of these components . Protein, DNA, and RNA based nanoparticles are often engineered from human viruses, plant viruses, and bacteriophages .…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles may be engineered from biological macromolecules (proteins, DNA, RNA), lipids, polymers, semiconductors, metals, or a vast number of possible combinations of these components . Protein, DNA, and RNA based nanoparticles are often engineered from human viruses, plant viruses, and bacteriophages .…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…There are a number of non-biodegradable polymers such as poly(methyl methacrylate) (PMMA), poly(acrylamide), poly(styrene), and poly(acrylates), (Banik et al 2016); however, chronic toxicity has been observed in studies using these materials. This has led a focus on biodegradable polymers (Burman et al 2015), examples of which include synthetic polymers such as poly(lactide) (PLA), poly(lactide-coglycolide) copolymers (PLGA), poly(ε-caprolactone) (PCL), and 17 and poly(amino acids) (Elsabahy and Wooley 2012).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…[1] Of particular interest is the ability to adapt www.advancedsciencenews.com www.advtherap.com Figure 3. [19,20] To further develop the utility of copolymers, an important consideration is biocompatibility, which can be imparted through the use of biodegradable subunits such as polyesters and polycarbonates. Reproduced with permission.…”
Section: Polymeric Nanoparticles As Therapeutic Platformsmentioning
confidence: 99%
“…[1] Copyright 2017, Elsevier. [18,19,24] The porosity of polymersomes has also been established by the insertion of channel proteins, such as OmpF or Aquaporin Z, creating channels for selective molecular transportation. Although there has been substantial progress toward the generation of polymersomes for biological applications, this is usually accomplished via the self-assembly of nonbiocompatible/degradable components comprising building blocks such as polystyrene (PS) and poly(dimethyl siloxane) (PDMS).…”
Section: Polymeric Nanoparticles As Therapeutic Platformsmentioning
confidence: 99%